Ecological-geographical issues of urban system development in Zhambyl region (ҚазҰУ Хабаршысы. География сериясы, 2025)
This article provides a comprehensive analysis of the ecological and geographical challenges faced by urban systems in the Zhambyl region of Kazakhstan, focusing on environmental issues such as air pollution, water contamination, and the degradation of natural ecosystems. The rapid pace of urbanization and industrialization in the region has led to significant changes in the ecological balance, with cities like Taraz and the Zualy district being major contributors to pollutant emissions. The study highlights the impact of these environmental problems on public health, biodiversity, and regional climate change.Using data from official reports, GIS technologies, and remote sensing, the article examines the distribution of pollutant emissions and identifies the key sources of pollution across various districts in the region. The results show that major industrial activities and high population density contribute to high levels of atmospheric pollution, while some districts, like Merken and Talas, have lower emission volumes due to less industrial development.The study suggests that addressing these challenges requires a multi-faceted approach, including the implementation of stricter environmental regulations, the adoption of eco-friendly technologies, improved waste management systems, and the promotion of sustainable resource management. The article emphasizes the importance of public engagement and environmental education in fostering a more sustainable urban future. By analyzing the current ecological situation, this study offers valuable insights for policymakers and local authorities to develop strategies that balance urban development with environmental protection and public health in the Zhambyl region.